The analysis of speed increase perspectives of nanostructuring burnishing with heat removal from the tool - Kuznetsov V. P. Viktor Pavlovich; Skorobogatov A. S.; Gorgots V. G.; Yurovskikh A. S. (Materials Science in Mechanical Engineering, 2016)
Title screen